Ketahanan Nasional dan Kesetaraan Gender: Reformasi Hukum Tata Negara Untuk Meningkatkan Partisipasi Perempuan di Sektor Pertahanan - Bagus Rosi, Muhammad (Kartika: Jurnal Studi Keislaman, 2025)
This study explores the interrelation between national resilience and gender equality with a particular focus on women’s participation in the defense sector. The research aims to critically examine how the constitutional and legal framework in Indonesia accommodates gender equality and what reforms are necessary to enhance inclusiveness in the defense field. Employing a qualitative approach with a normative juridical method, the study analyzes relevant constitutional provisions, statutory regulations, and secondary legal sources to identify both opportunities and structural barriers in policy implementation. The findings indicate that women’s participation in the defense sector remains minimal, primarily due to entrenched social constructions, discriminatory regulations, and the absence of affirmative legal measures that encourage gender mainstreaming. These limitations not only restrict women’s access to strategic positions but also weaken the holistic realization of national resilience. The study concludes that gender-sensitive constitutional reform is urgently required to ensure equality, foster inclusive participation, and strengthen national resilience in a sustainable manner.